2022
DOI: 10.1001/jamanetworkopen.2022.31790
|View full text |Cite
|
Sign up to set email alerts
|

Two-Year Health Outcomes in Hospitalized COVID-19 Survivors in China

Abstract: IMPORTANCERelatively little is known about the persistence of symptoms in patients with COVID-19 for more than 1 year after their acute illness. OBJECTIVE To assess the health outcomes among hospitalized COVID-19 survivors over 2 years and to identify factors associated with increased risk of persistent symptoms. DESIGN, SETTING, AND PARTICIPANTS This was a longitudinal cohort study of patients who survived COVID-19 at 2 COVID-19-designated hospitals in Wuhan, China, from February 12 to April 10, 2020. All pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
26
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 35 publications
(29 citation statements)
references
References 34 publications
2
26
1
Order By: Relevance
“…First domain (i.e., pre-COVID factors) describes risk factor present before SARS-CoV-2 infection and includes older age, female gender, higher BMI, and preexisting comorbidities (such as hypertension, diabetes, asthma, COPD, cardiac disease, chronic liver disease). 3,18,19,24,25 A conflicting report by Van Wambeke et al 26 showed that comorbidities did not correlate with long COVID, but rather with greater return to work. The second domain (i.e., COVID-related factors) describes risk factors present during acute infection with COVID-19 and includes severe infection, 3 and increased symptom burden.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…First domain (i.e., pre-COVID factors) describes risk factor present before SARS-CoV-2 infection and includes older age, female gender, higher BMI, and preexisting comorbidities (such as hypertension, diabetes, asthma, COPD, cardiac disease, chronic liver disease). 3,18,19,24,25 A conflicting report by Van Wambeke et al 26 showed that comorbidities did not correlate with long COVID, but rather with greater return to work. The second domain (i.e., COVID-related factors) describes risk factors present during acute infection with COVID-19 and includes severe infection, 3 and increased symptom burden.…”
Section: Discussionmentioning
confidence: 98%
“…These predictive factors are described in two domains. First domain (i.e., pre‐COVID factors) describes risk factor present before SARS‐CoV‐2 infection and includes older age, female gender, higher BMI, and pre‐existing comorbidities (such as hypertension, diabetes, asthma, COPD, cardiac disease, chronic liver disease) 3,18,19,24,25 . A conflicting report by Van Wambeke et al 26 showed that comorbidities did not correlate with long COVID, but rather with greater return to work.…”
Section: Discussionmentioning
confidence: 99%
“…The prevalence of anxiety in the severe group was significantly higher than that in the nonsevere group (severe vs. nonsevere: 10.2% vs. 5.9%; OR, 1.79; 95% CI: 1.17-2.76; P = 0.01). A total of 890 COVID-19 survivors aged 60 years and above participated in both one-year and two-year follow-up visits on symptom dynamics in a recent study [8]. Among these survivors, a prominent decreasing trend was found in most symptoms.…”
Section: Long-term Symptoms At the Two-year Follow-upmentioning
confidence: 99%
“…At the two-year follow-up, the median (IQR) score of CIS-fatigue was 8 (8-14) and 89 patients (7.7%) had scores of 27 or higher. Patients with severe disease had a nonsignificantly higher median (IQR) CIS-fatigue score (severe vs. nonsevere: 8 [8][9][10][11][12][13][14][15] vs. 8 [8][9][10][11][12][13]) and a higher proportion of patients with the CIS-fatigue score of at least 27 (severe vs. nonsevere: 9.8% [39 patients] vs. 6.6% [50 patients]) (Fig. 3A).…”
Section: Cis-fatigue Scores At the Two-year Follow-upmentioning
confidence: 99%
See 1 more Smart Citation